Effect of Chitosan-Based Edible Coating on the Quality and Shelf Life of Fresh Strawberries - Sahrial Hafids; Cahyaning Rini Utami; Ni Made Ayu Suardani Singapurwa (Agriculture Journal, 2025)
Strawberries (Fragaria × ananassa) are highly perishable fruits with limited shelf life, posing challenges to supply chains and consumer satisfaction. This study investigates the efficacy of chitosan-based edible coatings in extending the shelf life and preserving the quality of fresh Indonesian strawberries during refrigerated storage. The coating solution was prepared with 1.5% chitosan and applied via dipping, followed by storage at 4 ± 1˚C and 90% relative humidity for 12 days. Physical, chemical, and microbiological parameters including weight loss, firmness, color, total soluble solids, titratable acidity, Vitamin C retention, antioxidant activity, and microbial counts were systematically evaluated every 3 days. Results showed that chitosan coating significantly reduced weight loss and maintained higher firmness compared to uncoated controls. The coating also effectively preserved color by controlling lightness and redness (CIELAB parameters) and limited microbial proliferation, thereby extending the shelf life. Statistical analyses confirmed significant differences between coated and control groups from Day 6 onwards, with large effect sizes observed. These findings highlight the potential of chitosan edible coatings as a sustainable, low-cost postharvest technology to enhance strawberry quality and prolong shelf life under suboptimal cold chain conditions.